A leading indicator of house-price bubbles - Simon Juul Hviid (Danmarks Nationalbank, 2017)
Prior to the financial crisis in the mid-2000, house prices increased dramatically and most economists agree that part of the increase in Danish house prices can be characterized as a house- price bubble. The emergence of a house-price bubble can have sizeable implications for macroeconomic as well as financial stability. A house-price bubble is often a result of self-exciting beliefs, leading to explosiveness of the developments in house prices. This paper investigates the dynamics of house prices in Denmark in order to identify emerging bubbles in due time. We develop a fundamentals-adjusted house price index and apply the testing procedure of Phillips et al. (2015) to date-stamp house-price bubbles. The empirical results identify developments in line with a price bubble from mid-2005 in Denmark. When applied to flats in Copenhagen, real price developments in 2015-16 indicate speculative behaviour but it cannot be ruled out that developments are driven by fundamental economic factors. – – Forud for den finansielle krise i midten af 2000'erne steg huspriserne dramatisk, og de fleste økonomer er enige om, at en del af stigningen i huspriserne i Danmark havde karakter af en boligprisboble. Fremkomsten af en boligprisboble kan have betydelige konsekvenser for makroøkonomisk og finansiel stabilitet. En boligprisboble er som oftest et resultat af selvopfyldende forventninger, der fører til eksplosivitet i boligprisudviklingen. Dette arbejdspapir undersøger dynamikken i boligpriserne i Danmark for at kunne identificere bobler rettidigt. Vi opstiller et boligprisindeks, som er justeret for fundamentale faktorer, og anvender testproceduren i Phillips m.fl. (2015) til at identificere boligprisbobler. De empiriske resultater indikerer, at udviklingen fra midten af 2005 var i overensstemmelse med en prisboble i Danmark. Når testet anvendes på lejlighedspriser i København, så indikerer udviklingen i den reale pris i 2015-16 også spekulativ adfærd, men det kan ikke udelukkes, at udviklingen er drevet af fundamentale økonomiske faktorer.
Keywords: C22; G12; R31; 330; House price dynamics; right-tailed unit root tests; date-stamping bubble periods